Primary tumour location, molecular alterations, treatments, and outcome in a population-based metastatic colorectal cancer cohort - Emerik Osterlund; Klara Hammarström; Luís Nunes; Lucy Mathot; Artur Mezheyeuski; Tobias Sjöblom; Bengt Glimelius (BJC Reports)
Abstract Background Metastatic colorectal cancer (mCRC) patients in trials are selected. The aim was to study mCRC features population-based. Methods All 765 mCRC patients in the Uppsala region, Sweden, 2010–2020 were identified and analysed for RAS (n = 356/708) and BRAF-V600E (n = 123/708) mutations (mt) and deficient mismatch repair (dMMR, n = 58/643). Results Right colon primary tumours were associated with BRAF-V600Emt and dMMR and had worse median overall survival (mOS) than left colon or rectal mCRC. RAS&BRAF wildtype (wt) and proficient MMR were seen in 22%, 45%, and 31% of right colon, left colon, and rectum, respectively. Patients with right colon primaries received best supportive care only more often (34% vs 25% vs 24%) and metastasectomy less often (21% vs 31% vs 33%) than left colon and rectal primaries. In molecularly homogeneous subgroups (RAS&BRAFwt/RASmt/BRAF-V600Emt/dMMR) no difference in mOS were seen between right and left colon primaries, whereas rectal primaries had better mOS (26/15/8/9 vs 24/21/8/8 vs 32/23/6/NA months, respectively). This was also the case in homogenous treatment groups. Primary tumour location turned non-significant in multivariable OS analyses. Conclusions The high variation of BRAF-V600Emt, RASmt, dMMR, and treatment allocation population-based per primary tumour location explain the poor outcome in right-sided cancers.